A Robust Electrochemical Sensor for Determination of Thiamethoxam Based on Electrochemical Reduced Graphene Oxide-Cationic Pillar[6]arene Composite Film. Issue 12 (6th December 2021) - Wu, Yanju; Li, Zikang; Han, Dongyang; Duan, Qunpeng; Wang, Fei
Abstract : On the surface of a glassy carbon electrode, electrochemically reduced graphene oxide-cationic pillar[6]arene (ErGO-CP6) composite film was constructed using a pulsed potential method. UV–vis spectra, SEM, Raman spectra and electrochemical experiments were applied to characterize the composite film. It was then used as a new electrochemical sensing platform for determination of thiamethoxam. Due to the synergistic effect of ErGO and CP6, this composite film shows a higher sensitivity and better selectivity toward thiamethoxam than that of ErGO film. The linear range from 1.0 × 10 −7 to 1.3 × 10 −5 mol l −1 was obtained by differential pulse voltammetry. Meanwhile, the method was applied to cucumber and tomato samples in a recovery test. The recovery was between 92.0% and 98.7%, and the results are satisfactory. This study presents a promising electrochemical sensing platform for rapid and sensitive analysis of thiamethoxam.